Acoustic filters with a perforated tube - BRZÓZKA, Gerard (Archives of Acoustics, 1987)
A method of calculating acoustic properties of a low-pass filter with a perforated side baffle separating two wave-guides with constant cross-section areas is proposed. It is based on the principle of segmentation of the wave-guide into a series of elementary models which describe properties of acoustic element related to individual rows of perforation and segments of acoustic wave-guides, and on the description of acoustic properties of these models with the application of a transmission matrix with its properties of a chain matrix. Also relationships are given from which acoustic properties of a perforated baffle can be determined for a discrete parameter model at a laminar flow through orifices of the perforation. Moreover, a calculation model for determining generally applied measures – insertion loss and transmission loss – was proposed on the basis of the transmission matrix of an acoustic filter determined with the presented method.